SOME FEATURES OF DEVELOPMENT IN THE AGRICULTURAL POLICY WESTERN BALKAN CANDIDATES FOR MARKET ACCESS IN THE EU - Simonović, Zoran; Miletić, Slavomir; Popović, Vesna (Economics of Agriculture, 2019)
The agricultural policy of Western Balkan countries in the process of accession to the European Union market is characterized by high volatility, which is expressed in terms of the applied instruments and measures as well as the product concerned. In the first phase of liberalization of prices and trade, most countries abolished or significantly reduced the customs import and export barriers to a wide range of products and also reduced or eliminated production subsidies. Only import tariffs are the only basic protection instrument for producers. Input prices have increased considerably for producers, which has led to a decrease in income in agriculture. In reality, this meant that domestic agricultural production was left to the ruthless competition of EU countries that have far better developed agricultural and food production. In the past few years, the implementation of the new agrarian policy, in countries from the first round of accession candidates, the European Union has introduced budget support measures for producers, mainly in the form of payments per hectare or throat. These budget payments were made according to the model of the EU CAP.